Pengembangan Buku Aktivitas Anak Hebat sebagai Upaya Penerapan Gerakan 7 Kebiasaan Anak Indonesia Hebat di Kelas IV SDN 20 Cakranegara - Ni Made Kusumasari; Prayogi Dwina Angga; I Putu Herry Widhi Andika (Mataram University, 2026)
This study aims to determine the validity, practicality, and effectiveness of the great children activity book as an effort to implement the Gerakan 7 Kebiasaan Anak Indonesia Hebat in grade IV of SDN 20 Cakranegara. The method used in this study is Research and Development (R&D), with a 4D model consisting of define, design, develop, and disseminate. The subjects in this study were 27 grade IV students and one teacher at SDN 20 Cakranegara. The object of this study was the great children activity book, designed as an effort to implement the Gerakan 7 Kebiasaan Anak Indonesia Hebat. The data analysis techniques used were descriptive qualitative and quantitative. Data were collected using observation sheets, interview sheets, validity questionnaires, practicality questionnaires, and pretest/posttest questionnaires. The results showed that the media expert's validity was 90%, categorized as very valid, and the material expert's validity was 95,83%, categorized as very valid. The practicality level based on student responses in trial I was 90,87%, categorized as very practical, and in trial II, the practicality score was 88,27%, categorized as very practical. Furthermore, based on teacher responses in trial I, the practicality score was 91,66%, categorized as very practical, and in trial II, the practicality score was 97,22%, categorized as very practical. The effectiveness level, with an N-Gain score of 0,36, falls into the moderate category, indicating that the use of the great children activity book in implementing the Gerakan 7 Kebiasaan Anak Indonesia Hebat, is quite effective. Thus, the activity book developed is declared valid, practical, and effective, so that it can be used in implementing the Gerakan 7 Kebiasaan Anak Indonesia Hebat.